2022
DOI: 10.1016/j.jbc.2022.101648
|View full text |Cite
|
Sign up to set email alerts
|

The cap-proximal RNA secondary structure inhibits preinitiation complex formation on HAC1 mRNA

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…As anticipated, the ire1Δ and ire1Δ kin1Δ kin2Δ strains containing the HAC1-G771A allele grew on the medium containing tunicamycin ( Fig 3D , rows 2 and 6) and this growth was corelated the Hac1 protein expression from the un-spliced mRNA ( Fig 3E , lane 2). Consistent with the previous result(49), we also observed that Hac1 expression from the un-spliced HAC1-G771A mRNA was increased when cells were treated with ER stressor DTT ( Fig 3E ). Interesting, we observed that the ire1Δslt2Δ strain harboring the HAC1-G771A allele was unable to grow on the tunicamycin medium ( Fig 3D , row 4), even though a significant amount of Hac1 protein expression was detected when cells were grown in the absence or presence of DTT ( Fig 3E , lanes 3 and 4).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As anticipated, the ire1Δ and ire1Δ kin1Δ kin2Δ strains containing the HAC1-G771A allele grew on the medium containing tunicamycin ( Fig 3D , rows 2 and 6) and this growth was corelated the Hac1 protein expression from the un-spliced mRNA ( Fig 3E , lane 2). Consistent with the previous result(49), we also observed that Hac1 expression from the un-spliced HAC1-G771A mRNA was increased when cells were treated with ER stressor DTT ( Fig 3E ). Interesting, we observed that the ire1Δslt2Δ strain harboring the HAC1-G771A allele was unable to grow on the tunicamycin medium ( Fig 3D , row 4), even though a significant amount of Hac1 protein expression was detected when cells were grown in the absence or presence of DTT ( Fig 3E , lanes 3 and 4).…”
Section: Resultssupporting
confidence: 93%
“…To further confirm that the tunicamycin-resistant phenotype associated with the ER stress response was not solely due to expression of Hac1 protein, we examined the expression of Hac1 protein from the translationally de-repressed HAC1-G771A mRNA(49). We also assessed its influence on tunicamycin sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the overall direction of the PTE R domain emerging out from the cap-binding pocket in our docking models is similar to the crystal structure (PDB ID: 6O7Y) of a 5-nt capped RNA complexed with the Trypanosoma cruzi eIF4E homolog ( Fig. 5 F ), suggesting that the peripheral nucleotides of the SCV PTE beyond G18 have important roles in maintaining the shape-complementarity and specific interactions with the eIF4E, consistent with previous observations on the effect of sequence and secondary structures in binding eIF4E to the 5′ capped RNAs ( 48 , 49 ).…”
Section: Resultssupporting
confidence: 88%
“…The 5′ untranslated region (5′ UTR) of eukaryotic mRNAs plays important roles in regulating gene expression by affecting mRNA’s stability, location, and translation efficiency (van der Velden and Thomas 1999; Bashirullah, et al 2001; Mignone, et al 2002). It is generally believed that the functional impacts of 5′ UTR are mainly mediated by its sequence elements and structural features (Sobczak and Krzyzosiak 2002; Ding, et al 2012; Wang, et al 2016; Guo, et al 2017; Leppek, et al 2018; Uppala, et al 2022). One well-known 5′ UTR sequence element is the internal ribosome entry site (IRES), which enables the direct recruitment of the ribosome to the AUG initiation codon (Kozak 2005; Hinnebusch, et al 2016).…”
Section: Introductionmentioning
confidence: 99%